2015
DOI: 10.4014/jmb.1412.12075
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Glutamate Decarboxylase (GAD) from Lactobacillus sakei A156 Isolated from Jeot-gal

Abstract: A gamma-aminobutyric acid (GABA)-producing microorganism was isolated from jeot-gal (anchovy), a Korean fermented seafood. The isolate, A156, produced GABA profusely when incubated in MRS broth with monosodium glutamate (3% (w/v)) at 37°C for 48 h. A156 was identified as Lactobacillus sakei by 16S rRNA gene sequencing. The GABA conversion yield was 86% as determined by GABase enzyme assay. The gadB gene encoding glutamate decarboxylase (GAD) was cloned by PCR. gadC encoding a glutamate/GABA antiporter was loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 0 publications
5
35
0
Order By: Relevance
“…The enhancement in bioconversion ability appeared to be closely related to the increase in GAD activity. Previous studies showed that the activity of GAD could be increased by MnCl 2 (152%), CoCl 2 (118%), and ZnCl 2 (115%) (Sa et al, 2015), which was consistent with increased R GLu detected in this study (114%, 191%, and 416%, respectively). Besides, a positive effect of MgSO 4 (125%) was also observed, as described by Ueno et al (1997).…”
Section: Effect Of Metal Ions On L-glutamate Bioconversionsupporting
confidence: 92%
“…The enhancement in bioconversion ability appeared to be closely related to the increase in GAD activity. Previous studies showed that the activity of GAD could be increased by MnCl 2 (152%), CoCl 2 (118%), and ZnCl 2 (115%) (Sa et al, 2015), which was consistent with increased R GLu detected in this study (114%, 191%, and 416%, respectively). Besides, a positive effect of MgSO 4 (125%) was also observed, as described by Ueno et al (1997).…”
Section: Effect Of Metal Ions On L-glutamate Bioconversionsupporting
confidence: 92%
“…Different ions can affect the stability and activity of GAD from different sources ( Table 2). GAD from E. avium M5 is activated in the presence of CaCl2 and MnCl2 but the activity is decreased by CuSO4 and AgNO3 [82]; comparable results were also obtained for GAD from other LAB sources, L. zymae [46] and L. sakei A156 [80].…”
Section: Biochemical Insights Into Glutamate Decarboxylase From Lactisupporting
confidence: 69%
“…As mentioned above, a number of LAB carry two GAD-encoding genes, gadA and gadB. Frequently, studies have focused on the purification and characterization of GadB, e.g., from E. raffinosus [75], L. plantarum [79], L. brevis [78], L. sakei [80], L. paracasei [18] since the expression levels of recombinant GadB are typically higher than those for GadA [55]. A recent study by Wu et al showed that gadA transcript was highly upregulated (55-fold) in strain L. brevis NPS-QW-145 at the stationary phase of growth.…”
Section: Biochemical Insights Into Glutamate Decarboxylase From Lactimentioning
confidence: 99%
“…cremoris MG1363 and L. buchneri NRRL B-30929. However, there is no evidence that the gadR gene exists in other LAB species, except for strain L. sakei A156, the genome sequence of which has not yet been published [ 36 ]. In line with these differences, gadC and gadB of L. brevis and those genes of L. sakei share high sequence identity but are more distantly related to these genes in L. lactis , L. reuteri and L. plantarum .…”
Section: Resultsmentioning
confidence: 99%